Coverage of the ISO 21500 Standard in the Context of Software Project Management by a Simulation-Based Serious Game - Calderón, Alejandro; Ruiz, Mercedes; O’Connor, Rory V. (Software Process Improvement and Capability Determination, 2017)
Bringing professional practice into the learning/teaching process is an especially difficult task in the scope of software project management and can turn into a challenge in the context of software process standards education. The ISO 21500 standard is an international reference standard that provides generic guidance and good practices in project management. In this paper, we perform a literature review in order to analyze the current studies related to the use of serious games for understanding, teaching and supporting the education of the ISO 21500 standard. Moreover, we propose ProDec, a serious game for software project management training, and provide a mapping between the different stages of the game lifecycle and the ISO 21500 standard applying its management processes in the context of software projects. As a result, we observe that in this context, ProDec is able to cover seven of the ten subject groups and almost 75% of the project management processes of the ISO 21500 standard.